Group skills and organizational communication in times of COVID-19 - Corrales Peralta, Freddy Leonidas; Neira Ponce, Elsa Emma (VISUAL REVIEW. International Visual Culture Review / Revista Internacional de Cultura Visual, 2022)
The present investigation carries out its studies in educational institutions of the primary education sector, pretending to know if, in times of pandemic, the director's group skills are correlated with organizational communication, the investigation began with a sample of 96 teachers who responded to a survey relating the dimensions of organizational communication and the group skills of the directors, the conclusions corroborated that the skills of the director in times of COVID-19 have been modified and have increased, verifying the hypothesis that the group skills of the director in times of the COVID pandemic -19 are significantly related to organizational communication.